Symposium 4: A Feeling or a Practice? Achieving Interculturality In an eLearning Course - Banks, Sheena; McConnell, David; Bowskill, Nicholas (Proceedings of the International Conference on Networked Learning, 2008)
This paper discusses findings from a research study of a Sino-UK online course about the impact of intercultural understanding of e-learning in an online course, involving UK and Chinese higher education practitioners that was jointly designed by a UK and Chinese team. This topic is important because of current policy trends where technology has become one of the key drivers of globalization. Drawing on research data from computer mediated communication in the course, the paper considers processes and factors related to course design that may foster or impede intercultural understanding. The main conclusion of the paper is that course design has an important impact on the successful outcomes of intercultural e-learning, particularly a course design that creates an online learning community where learners can build social relationships and trust to share knowledge, values and goals that facilitate collaborative learning about cultures. Emerging findings are that styles of computer mediated communication can enhance or adversely affect intercultural e-learning and a strong link between social presence and learner support is needed. Finally, the paper identifies the need for more research for the development of good practice.